2014
DOI: 10.1190/geo2013-0427.1
|View full text |Cite
|
Sign up to set email alerts
|

Full-wavefield inversion of surface waves for mapping embedded low-velocity zones in permafrost

Abstract: Surface waves are advantageous for mapping seismic structures of permafrost, in which irregular velocity gradients are common and thus the effectiveness of refraction methods are limited. Nevertheless, the complex velocity structures that are common in permafrost environments often yield unusual dispersion spectra, in which higher-order and leaky modes are dominant. Such unusual dispersion spectra were prevalent in the multichannel surface-wave data acquired from our permafrost study site at Barrow, Alaska. Ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…The principles of MASW methods have been successfully used for in situ studies, for example, the methodology employed by Ryden and Park () to determine the thickness and shear velocities of pavement layers. These concepts have already been used in other systems with similar characteristics (e.g., permafrost study by Dou & Ajo‐Franklin, ). An interesting study for soil structure was presented by Mandal et al () for linking soil strength with P wave velocities.…”
Section: Geophysical Methods In Soil Sciencementioning
confidence: 99%
“…The principles of MASW methods have been successfully used for in situ studies, for example, the methodology employed by Ryden and Park () to determine the thickness and shear velocities of pavement layers. These concepts have already been used in other systems with similar characteristics (e.g., permafrost study by Dou & Ajo‐Franklin, ). An interesting study for soil structure was presented by Mandal et al () for linking soil strength with P wave velocities.…”
Section: Geophysical Methods In Soil Sciencementioning
confidence: 99%
“…Site core samples at 3-6 m depth [O'Sullivan, 1966;Brown, 1969;Sellmann et al, 1975] have shown salinity values up to 2 times seawater salinity [O'Sullivan, 1966]. Bulk electrical resistivity imaging, seismic, and analysis of core samples at the study site [Dou and Ajo-Franklin, 2014;Dafflon et al, 2016] suggested that the partially unfrozen saline permafrost is spatially extensive and heterogeneous.…”
Section: Site Description and Study Transectsmentioning
confidence: 99%
“…Inverting surface waves for the S-wave velocity model fall into two categories: 1) the classical method of inverting dispersion curves (Evison et al, 1959;Park et al, 1998;Xia et al, 2004) for a 1D layered medium, and 2) waveform inversion (Groos et al, 2014;Solano et al, 2014;Dou and Ajo-Franklin, 2014) for 2D and 3D media. The classical method accurately inverts for a 1D S-wave velocity model, but becomes less accurate with increasing lateral heterogeneity in the subsurface velocity model.…”
Section: Introductionmentioning
confidence: 99%